A novel thermal criterion for bubble destruction in hydrodynamic cavitation: numerical modeling and experimental validation - Pavlenko, Anatoliy (International Conference “Environmental Engineering”, 2026)
This research investigates the conditions precipitating the surface instability of spherical bubbles and develops a novel thermal criterion for their terminal collapse during hydrodynamic cavitation. A new mathematical model of vapour bubble dynamics was formulated and implemented in numerical simulations, accounting for heat and mass transfer processes at the bubble interface under various flow conditions. The central hypothesis of the model posits that bubble collapse is triggered when the surface temperature exceeds a critical threshold. Theoretical findings were validated through comparison with experimental data acquired via Venturi tube measurements.